In vivo protective role of human group IIa phospholipase A2 against experimental anthrax - Piris-Gimenez, Alejandro; Paya, Miguel; Lambeau, Gérard; Chignard, Michel; Mock, Michèle; Touqui, Lhousseine; Goossens, Pierre L (The Journal of immunology (1950), 2005)
Anthrax is an acute disease caused by Bacillus anthracis. Some animal species are relatively resistant to anthrax infection. This trait has been correlated to the extent of the local inflammatory reaction, suggesting innate immunity to be the first line of defense against B. anthracis infection in nonimmunized hosts. Group IIA secreted phospholipase A2 (sPLA2-IIA) is produced in particular by macrophages and possesses potent antibacterial activity especially against Gram-positive bacteria. We have previously shown in vitro that sPLA2-IIA kills both germinated B. anthracis spores and encapsulated bacilli. Here we show that sPLA2-IIA plays in vivo a protective role against experimental anthrax. Transgenic mice expressing human sPLA2-IIA are resistant to B. anthracis infection. In addition, in vivo administration of recombinant human sPLA2-IIA protects mice against B. anthracis infection. The protective effect was observed both with a highly virulent encapsulated nontoxinogenic strain and a wild-type encapsulated toxinogenic strain, showing that toxemia did not hinder the sPLA2-IIA-afforded protection. sPLA2-IIA, a natural component of the immune system, may thus be considered a novel therapeutic agent to be used in adjunct with current therapy for treating anthrax. Its anthracidal activity would be effective even against strains resistant to multiple antibiotics.